Characterization of the Streptomyces coelicolor A3(2) wblE gene, encoding a homologue of the sporulation transcription factor - Homerová, D; Sevcíková, J; Kormanec, J (Folia microbiologica, 2003)
The gene corresponding to the recently identified whiB-paralogous gene wblE in S. coelicolor was found after sequencing the downstream region of the stress-response sporulation-specific sigma-factor gene, sigH, in S. coelicolor A3(2). Sequence analysis has revealed an ORF exhibiting high similarity to sporulation transcription factors WhiB and WhiD. A stable null mutant of the wblE gene was obtained by integrative transformation, via double cross-over. Disruption of the S. coelicolor wblE gene appeared to have no obvious effect on growth, morphology, differentiation, and production of the pigmented antibiotics actinorhodin and undecylprodigiosin. Expression of the wblE gene was investigated during differentiation by S1 nuclease mapping, using RNA prepared from S. coelicolor A3(2) and its isogenic sigF and sigH mutants grown to various developmental stages. A single promoter was identified upstream of the wblE coding region. The wblEp promoter was induced at the beginning of aerial mycelium formation and its activity decreased later in differentiation. No differences in expression of the wblEp promoter were detected in S. coelicolor A3(2) mutants in sigF and sigH genes for sporulation-specific sigma factors. Sequence of the wblEp promoter showed partial similarity to the consensus sequence of the extracytoplasmic sigma factors.
Keywords: bakteriální RNA; sekvence nukleotidů; vývojová regulace genové exprese; Streptomyces; Sequence Homology; Gene Expression Regulation, Developmental; spory bakteriální; molekulární sekvence - údaje; Amino Acid Sequence; promotorové oblasti (genetika); regulace genové exprese u bakterií; sekvenční homologie; DNA, Bacterial; DNA bakterií; prodigiosin; Anthraquinones; Genes, Bacterial; Prodigiosin; Transcription Factors; transkripční faktory; Spores, Bacterial; inzerční mutageneze; Promoter Regions, Genetic; sekvence aminokyselin; anthrachinony; Molecular Sequence Data; Base Sequence; RNA, Bacterial; Mutagenesis, Insertional; bakteriální geny; Gene Expression Regulation, Bacterial